Islamisasi Ilmu - Firman Firman; Bahaking Rama; Muhammad Yahdi (Edu Sociata : Jurnal Pendidikan Sosiologi, 2023)
Islamic civilization has progressed because knowledge has received high appreciation from Muslims and the teachings of Islam itself. This is what encouraged the Umayyad and Abbasid caliphates to be very concerned and gave rise to many Islamic educational institutions which became places to study and deepen knowledge and within a certain period of time became the cause of the emergence of many scientists which ultimately gave birth to many works that could be read and became references for scientists. . However, after the glory days of the classical era and Muslim nations lagging behind in the scientific field, both social sciences and science, as well as the shift of the direction of knowledge to the Western world, people who want to explore various branches of science and knowledge will get what they want. look in Western European countries or in Japan. In fact, Islamic religious studies are no longer dominated by Middle Eastern countries but are almost entirely pioneered by Western scientists and scholars. As a result, the science that developed was formed from Western philosophical thought which was influenced by secularism, utilitarianism and materialism. As a result of this, the sacredness of knowledge is lost due to efforts to separate revelation from human reason. Based on this, an idea emerged to bring together the advantages born of human thought with a touch of revelation so that new science is modern but still religious and has the breath of monotheism. This idea became known as the Islamization of science.